Disfungsi PP Nomor 45 Tahun 1990 Tentang Pembagian Gaji Pasca Perceraian PNS: (Studi Kasus di Pengadilan Agama Bojonegoro) - Rofrofil Akmal, Ahmad Wildan; Hakim, Aunul; Toriquddin, Moh (Muhammadiyah University of Surabaya, 2025)
Divorce among civil servants (PNS) has been increasingly prevalent in Bojonegoro Regency over the past four years. The majority of these cases are dominated by domestic violence (KDRT) and infidelity. There are specific regulations in Government Regulation No. 45 of 1990 concerning civil servants' benefits, which indicate that the status of civil servants is different from that of the general public. This study focuses on the dysfunction of Article 8, which governs the division of one-third of a civil servant’s salary after divorce. This research uses empirical legal research or field research with a qualitative approach. Primary data was obtained from semi-structured interviews with religious court judges in Bojonegoro. The findings of this study reveal that Article 8, which regulates the division of civil servant salaries, is not fully implemented in the Bojonegoro state court or experiences dysfunction. This is due to the potential harm that may arise after the divorce if it is applied in civil servant divorce cases, such as the continued use of alimony by the ex-wife from her former husband until she remarries. This also opens the possibility that if the ex-wife enters into a religious marriage, alimony from the ex-husband will continue to be paid to the ex-wife and her new husband.